2017
DOI: 10.1136/bmjopen-2016-013568
|View full text |Cite
|
Sign up to set email alerts
|

Workplace violence against physicians in Turkey’s emergency departments: a cross-sectional survey

Abstract: ObjectiveWe aimed to determine the prevalence of violence directed at emergency department (ED) physicians in Turkey and confirm the factors influencing such violence.DesignCross-sectional survey study.SettingCountry of Turkey.ParticipantsPhysicians currently practising in EDs in Turkey.Main outcome measuresThe prevalence of violence directed at physicians and factors that may influence it, such as physicians’ personal characteristics, ED characteristics and physicians’ opinions regarding the causes of and sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
63
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 30 publications
9
63
1
2
Order By: Relevance
“…4,15 Although WPV is a global health problem, recent studies have reported a higher magnitude of WPV in low and middle-income countries (LMICs). 3,[16][17][18] Critical factors including severe scarcity of human resources for health, 19 overworking and burnout in overcrowded hospitals, 20 lack of adequate facilities and logistics to deliver health services, 19,21 pre-existing sociobehavioral problems of the patients and healthcare providers, 16,19,22 high cost of availing health services, 23,24 lack of appropriate security measures, 25,26 and many more, are found to be associated with WPV in resource-constrained contexts. A high burden WPV is reported in China where about one-third of the doctors have faced some violence and thousands have been reported to be assaulted viciously.…”
Section: Introductionmentioning
confidence: 99%
“…4,15 Although WPV is a global health problem, recent studies have reported a higher magnitude of WPV in low and middle-income countries (LMICs). 3,[16][17][18] Critical factors including severe scarcity of human resources for health, 19 overworking and burnout in overcrowded hospitals, 20 lack of adequate facilities and logistics to deliver health services, 19,21 pre-existing sociobehavioral problems of the patients and healthcare providers, 16,19,22 high cost of availing health services, 23,24 lack of appropriate security measures, 25,26 and many more, are found to be associated with WPV in resource-constrained contexts. A high burden WPV is reported in China where about one-third of the doctors have faced some violence and thousands have been reported to be assaulted viciously.…”
Section: Introductionmentioning
confidence: 99%
“…Workplace violence (WPV) by patients and visitors is a reality in many emergency departments (ED) all over the world [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Previous studies have shown that in North America and Great Britain, 74% of doctors were victims of verbal abuse (VA) and 28% were victims of physical abuse (PA) over a one year period.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] In other parts of the world also, several studies have been conducted. [31][32][33][34][35][36][37] By means of their all India surveys, Indian Medical Association (IMA) have reported that 75% doctors had experienced violence and 82.7% felt stressed out. 3,5,10 Nonetheless, there exits a dearth of qualitative studies on this problem.…”
mentioning
confidence: 99%